Incidence of twisted disease and cultivation practice of shallot farmers in Bantul coastal area, Yogyakarta, Indonesia - Wibowo, Arif; Santika, Islaminati Anna; Syafitri, Luthfiana Mifta; Widiastuti, Ani; Subandiyah, Siti; Harper, Stephen (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
Shallot (Allium cepa var. aggregatum L.) is an important commodity in horticulture and Indonesian foods. In Bantul Regency, Yogyakarta, Indonesia, shallot twisted diseases caused by Fusarium spp. significantly reduced yield quality and quantity. Supportive condition for plant-pathogen interaction needed for twisted disease development. This research aimed to measure the twisted disease incidence and observe the cultivation practice applied by shallot farmers in the Bantul coastal area as environmental aspects of the twisted disease to be a pre-study for further research on metagenomic analysis. This research had conducted in three sub-villages with different agroecosystems in the coastal area: Sono, Samiran, and Depok. Data were collected in shallot cultivation period in dry and rainy seasons from three farmers of each area. The higher disease incidence in the rainy season occurred in the Samiran sub-village at 33.97%, while in the dry season, disease incidence occurred in the Depok sub-village at 20.14%. Sono sub-village had the lowest disease incidence in rainy and dry seasons at 12.44% and 0%. Farmer cultivation practice may drive disease incidence due to environmental factors such as shallot variety, spacing between plants, fertilizer, and fungicides. Hence, further study is needed to understand plant-pathogen interaction with metagenomics through samples from 2 and 6 WAP in rainy seasons.